A boy with blistering of sun-exposed skin and finger shortening: the first case of Variegate Porphyria with a novel mutation in protoporphyrinogen oxidase (PPOX) gene in Iran: a case report and literature review - Mohammad Vafaee-Shahi; Saeide Ghasemi; Aina Riahi; Zahra Sadr (BMC, 2022)
Abstract Variegate Porphyria (VP) is an inherited rare disorder that is caused by mutations in the protoporphyrinogen oxidase (PPOX) gene. This deficiency is associated with the accumulation of porphyrins and porphyrin precursors in the body, which, in turn, can potentially result in a variety of skin and neurological symptoms. Here, we reported a 7-year-old boy with homozygous VP and novel mutation on PPOX gene. He was admitted with three episodes of generalized tonic-clonic seizure in the last 6 months. He was presented with lesions, hyperpigmentation, fragility, and blistering of sun-exposed skin. The weakness of limbs and brachydactyly were observed. In the follow-up, he had aggressive behavior, learning disability and abdominal pain, particularly around the navel. Eventually, the whole exome sequencing (WES) result reported a novel homozygous pathogenic variant (c.1072G > A p.G358R) in PPOX gene which confirmed the VP. He had been advised to be away from the sun and use sunscreen regularly.